Cranial ultrasonography in diagnosis of infantile cerebral cavernous malformation - Shuya Kaneko; Iku Ikeno; Hideo Wada (Clinical Case Reports)
Abstract The case of an infantile cerebral cavernous malformation detected by transfontanelle cranial ultrasonography. Infantile cerebral cavernous malformations tend to cause more major bleeding compared to those in older groups, so early detection and treatment are crucial. Cranial ultrasonography can contribute to the early diagnosis of infantile cerebral cavernous malformations.